Promoting transdisciplinary collaboration in academia: uniting for climate-resilient health - Qamar, Wajiha; Qayum, Mehran; Nisa, Waqar un; Khaleeq, Nadia; Ali, Asma (Frontiers in Climate, 2024)
In a world where some regions are directly experiencing the effects of the climate change, while others are more vulnerable; this article dives into the deep and frequently catastrophic impact of the climate change on vulnerable countries. This review emphasizes the need for transdisciplinary academic collaboration, including social scientists, healthcare professionals, engineers, policy experts, and climate scientists, and underscores academia’s potential role in advancing climate-resilient health systems in these areas. The study promotes inclusive research that prioritizes at-risk groups, involves communities, and supports culturally sensible methodologies. Beyond their traditional tasks, academia has an obligation for action, learning, innovation, and change. To address the complex health concerns brought on by the planetary crisis, collaboration across academic fields and in tandem with communities, governments, and international organizations is crucial. Ongoing collaboration between academia, governments, and stakeholders is crucial to developing healthcare systems and technologies that are climate resilient. The complex role of academia involves developing pioneering solutions in healthcare for a sustainable future, advocating for policies based on evidence, and educating the next generation of professionals.